Physical fitness assessment of MSKPPM Kedah veteran football players - Mohd Yusof Zulkifli, Syed Ambon Syed Ahmad Ezahar, Mohamad Hashim Junaidy, (Universiti Pendidikan Sultan Idris, 2016)
Physical fitness assessment of MSKPPM Kedah veteran football players by Mohd Yusof Zulkifli, Syed Ambon Syed Ahmad Ezahar, Mohamad Hashim Junaidy,